Evaluación de un Protocolo de IATF (Inseminación Artificial a Tiempo Fijo) con Progestágenos y ECG (Gonadotrofina Coriónica Equina) post retiro del implante en Ganado Bovino en la Hacienda Las Lomas. - Caluña Tipán, Ruth Noemí (2018)
The present investigation was carried out in Las Lomas state located in Latacunga Canton, Tanicuchi parish with the objective of evaluating a protocol of IATF (Fixed Time Artificial Insemination) with progestogens and eCG (Equine Chorionic Gonadotropin) after implant removal. 27 cows of the Holstein breed were selected; in the same conditions of management, feeding, with a body condition of 3, ages between 15 and 18 months and ovarian condition of the corpus luteum for all. The animals that presented estrus were evaluated, their gestation was confirmed and the cyclicity of the same post-IATF protocol. The protocol was applied, starting on day 0 with the application of 0.25 ml of Estradiol Benzoate (BE) plus the insertion of the CIDR device of 1.38 g, on day 8 the device was removed and the application of 2 ml of Cloprostenol (Estrumate). Then the administration of 200 IU of eCG (day 9) was carried out and Artificial Insemination was performed 50 hours after removal of the implant (day 10). Records of the animals were kept depending on the time that each of the research processes was carried out. The evaluation of the IATF protocol determined that the number of pregnant animals was 23, the animals that repeated oestrus (3), and only 1 animal was not confirmed the gestation and did not show signs of heat in the subsequent sexual cycle (17 to 24 days) that normally should be presented. Allowing also to improve the reproductive aspects of the herd, by accelerating the production process, being able to apply to other states and / or small producers that have problems with their dairy herds, thus promoting better results and economic income of production.